PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PADA BPKPD KOTA SURABAYA - Chairina, Frista; Wehartaty, Tineke (Widya Mandala Surabaya Catholic University, 2019)
A good financial report is a financial statement containing and financial analysis. Improving the quality of financial statements in the municipal government sector in presenting financial statements in accordance with the Financial Accounting Standards (SAK) and Government Accounting Standards (SAP) that can not be issued from the efforts of the city government. Implementation of information systems is one effort to achieve the quality of financial statements, given the purpose of government financial reporting is for public accountability.This research was conducted at Surabaya City Financial and Tax Administration Board (BPKPD) implementing online finance software application (e-accounting) in year 2016. This study aims to analyze and prove the influence of application of accounting information system to the quality of financial statements at Financial and Tax Administration Board (BPKPD) of Surabaya. The results showed that the application of accounting information systems affect the quality of financial statements, meaning Utilization accounting information system helps BPKPD in providing quality financial information.